Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$G$ is a group where $H$ is a subgroup of $G$ with index $[G:H]< +\infty$. Show if for the element g is an element in G we have $gHg^{-1}$ is a subset of H. Then we must have$ gHg^{-1}=H$.

(This is not necessarily true if $[G:H]= +\infty)$

Just came to this question while looking for problems. I would like to know how to prove this.

Here is what I did

for all $x^2 = e $

$$x\rightarrow x^{-1}=x$$ $$y\rightarrow y^{-1}$$ $$xy\rightarrow (xy)^{-1} = y^{-1}x^{-1}$$

Let $T_g: x\mapsto g^{-1}(x)(g)$. Let $G: g\mapsto g^{-1}xg = X$ where this is homomorphic Then $gh\rightarrow T_{gh} (x) = (gh)^{-1}xg$. Not sure how to solve. Please help.

share|cite|improve this question
I removed the (measure-theory) and (general-topology) tags which were not appropriate. – Sammy Black Mar 21 '13 at 4:06
@9959: notice $H=ege^{-1}\subset gHg^-1$ and $|gHg^-1|=|H|$ – Maisam Hedyelloo Mar 21 '13 at 4:08
Where did $T$ suddenly come from. And when you write $Tsub(g)sub(h)$ do you mean $T_{g}T_h$? – Thomas Andrews Mar 21 '13 at 4:16
Do you mean $T_{gh}$ by Tsub(g)sub(h)? You can typeset it like this: $T_{gh}$. – Martin Sleziak Mar 21 '13 at 4:16
For some basic information about writing math at this site see e.g. here, here, here and here. – Martin Sleziak Mar 21 '13 at 4:17

If $[G:H]=n$ is finite, $G$ can be written as a disjoint union of $n$ cosets of $H$, $G=\bigcup_{1\le i\le n} a_i H$. Conjugating this by $g$ expresses $G$ as a disjoint union of $n$ cosets of the subgroup $gHg^{-1}$: $$G=\bigcup_{1\le i\le n} ga_i H g^{-1}=\bigcup_{1\le i\le n} (ga_ig^{-1})( g H g^{-1}),$$ so $[G:gHg^{-1}]=n$. However, if $gHg^{-1}\le H$, then also $$ [G:gHg^{-1}]=[G:H][H:gHg^{-1}]. $$ Cancelling $n$ from both sides then gives $[H:gHg^{-1}]=1$, so $H=gHg^{-1}$.

share|cite|improve this answer

Conjugating by $g$ is an automorphism of $G$. So, if $H$ is a subgroup of finite index then $gHg^{-1}$ is also a subgroup of finite index and $[G:H]=[G:gHg^{-1}]$. Therefore if $gHg^{-1}\subseteq H$, then $H=gHg^{-1}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.